"Sheddable" PEG-lipid to balance the contradiction of PEGylation between long circulation and poor uptake. Issue 20 (11th May 2016) - Zhao, Caiyan; Deng, Hongzhang; Xu, Jing; Li, Shuyi; Zhong, Lin; Shao, Leihou; Wu, Yan; Liang, Xing-jie
Abstract : A "sheddable" PEG-lipid micelle was prepared to balance the contradiction between long circulation and poor uptake of traditional PEGylated nanoparticles. Abstract : PEGylated lipids confer longer systemic circulation and tumor accumulation via the enhanced permeability and retention (EPR) effect. However, PEGylation inhibits cellular uptake and subsequent endosomal escape. In order to balance the contradiction between the advantages of long circulation and the disadvantages of poor uptake of PEGylated lipids, we prepared a "sheddable" PEG-lipid micelle system based on the conjugation of PEG and phosphatidyl ethanolamine (DSPE) with a pH sensitive benzoic imine bond. In a physiological environment, the PEG-protected micelles were not readily taken up by the reticuloendothelial system (RES) and could be successfully delivered to tumor tissue by the EPR effect. In a tumor acidic microenvironment, the PEG chains detached from the surfaces of the micelles while the degree of linker cleavage could not cause a significant particle size change, which facilitated the carrier binding to tumor cells and improved the cellular uptake. Subsequently, the "sheddable" PEG-lipid micelles easily internalized into cells and the increased acidity in the lysosomes further promoted drug release. Thus, this "sheddable" PEG-lipid nanocarrier could be a good candidate for effective intracellular drug delivery in cancer chemotherapy.